Kiai Religious Authority and Discourse of Power in Post-Lunar Eclipse Almsgiving Determinations Through Hannah Arendt and Hadith Perspectives - Arfan, Nuril Aisyah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to examine the forms of religious authority of kiai in the determination and implementation of post-lunar eclipse almsgiving practices in Ketapang Village, Sampang, Madura, and to analyze how the discourse of power strengthens kiai legitimacy when analyzed through Hannah Arendt’s and hadith perspectives. This qualitative research employs an ethnographic approach. The data consist of information on religious authority construction, power discourse, and almsgiving practices, sourced from four kiai and fifteen community members in Ketapang Village. Data collection techniques include in-depth interviews with kiai and community members, participant observation of religious gatherings and eclipse-related rituals, and documentation of classical Islamic texts (kitab kuning) and religious pronouncements. Data analysis employs thematic analysis with stages of data reduction, data presentation, and conclusion drawing, integrating Hannah Arendt’s political philosophy framework with hadith studies methodologies. The findings demonstrate that kiai religious authority is constructed through textual mastery, interpretive competence, and community recognition, while power discourse operates through theological legitimation, social networks, and performative practices. The interaction between religious authority and social power creates community compliance through mechanisms of trust, cultural tradition, and spiritual charisma. This research contributes theoretically to understanding the dynamics of religious authority in contemporary Islamic communities and pragmatically provides insights into the negotiation between classical texts and modern social realities.